2014
DOI: 10.1002/anie.201309066
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Metallo DNA Duplex Containing Consecutive Watson–Crick‐like T–HgII–T Base Pairs

Abstract: The metallo DNA duplex containing mercury-mediated T-T base pairs is an attractive biomacromolecular nanomaterial which can be applied to nanodevices such as ion sensors. Reported herein is the first crystal structure of a B-form DNA duplex containing two consecutive T-Hg(II)-T base pairs. The Hg(II) ion occupies the center between two T residues. The N3-Hg(II) bond distance is 2.0 Å. The relatively short Hg(II)-Hg(II) distance (3.3 Å) observed in consecutive T-Hg(II)-T base pairs suggests that the metallophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(147 citation statements)
references
References 59 publications
5
138
1
3
Order By: Relevance
“…30 Previous studies have demonstrated that T-Hg II -T base pairs exhibit similar thermal stabilities and structural features as T-A base pairs in duplex DNA. [10][11][12] The perception of analogous behavior of T-Hg The kinetic parameters of mercury binding reactions are expected to be highly relevant in vivo, where high concentrations of protein thiols and glutathione (20 -50 mM total) would be expected to easily out-compete DNA for Hg II binding. 31 Amazingly, the addition of micromolar concentrations of Hg II (5 µM) to living cells resulted in the formation of highstability DNA-Hg II adducts at a frequency of 0.3% of all base pairs.…”
Section: Discussionmentioning
confidence: 99%
“…30 Previous studies have demonstrated that T-Hg II -T base pairs exhibit similar thermal stabilities and structural features as T-A base pairs in duplex DNA. [10][11][12] The perception of analogous behavior of T-Hg The kinetic parameters of mercury binding reactions are expected to be highly relevant in vivo, where high concentrations of protein thiols and glutathione (20 -50 mM total) would be expected to easily out-compete DNA for Hg II binding. 31 Amazingly, the addition of micromolar concentrations of Hg II (5 µM) to living cells resulted in the formation of highstability DNA-Hg II adducts at a frequency of 0.3% of all base pairs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact a review was recently published [36], however the number of X-ray structures is still limited [10]. To this respect, the structure of a duplex with the thymineHg-thymine (N(3)-Hg-N(3)) recognition pattern has been recently described [37], which is similar to the previously described for bis(1-methylthyminato)mercury(II) [34] complex. Moreover, the coordination of Hg(II) to O(4) atom has been described in a mercuric chloride complex with uracil and dihydrouracil [35].…”
Section: Crystal Structurementioning
confidence: 77%
“…52 The structure of THg II T pairs inside DNA duplexes has recently been characterized by NMR spectroscopy 53 as well as X-ray crystallography. 54 As for RNA derivatives, the formation of Hg(II)-mediated uracil base pairs (UHg II U) was demonstrated within RNA duplexes. 55 Most recently, a fluorescent analogue of T has been reported that is a promising artificial nucleobase to study the formation of T Hg II T base pairs by fluorescence spectroscopy.…”
Section: Hg(ii)-mediated Base Pairingmentioning
confidence: 99%